Convergent evolution of complex genomic rearrangements in two fungal meiotic drive elements - Svedberg, Jesper; Hosseini, Sara; Chen, Jun; Vogan, Aaron A; Mozgova, Iva; Hennig, Lars; Manitchotpisit, Pennapa; Abusharekh, Anna; Hammond, Thomas M; Lascoux, Martin; Johannesson, Hanna (Nature communications, 2018)
Meiotic drive is widespread in nature. The conflict it generates is expected to be an important motor for evolutionary change and innovation. In this study, we investigated the genomic consequences of two large multi-gene meiotic drive elements, Sk-2 and Sk-3, found in the filamentous ascomycete Neurospora intermedia. Using long-read sequencing, we generated the first complete and well-annotated genome assemblies of large, highly diverged, non-recombining regions associated with meiotic drive elements. Phylogenetic analysis shows that, even though Sk-2 and Sk-3 are located in the same chromosomal region, they do not form sister clades, suggesting independent origins or at least a long evolutionary separation. We conclude that they have in a convergent manner accumulated similar patterns of tandem inversions and dense repeat clusters, presumably in response to similar needs to create linkage between genes causing drive and resistance.
Keywords: rekombinace genetická; Chromosomes, Fungal; genom fungální; Genetic Linkage; genomika; chromozomy hub; Genomics; Phylogeny; Genome, Fungal; Recombination, Genetic; fylogeneze; genetická vazba; Neurospora